Interview with David Woodruff: “Financial Market Governs by Panic” - WoodruffDavid M. (Journal of Economic Sociology, 2016)
David Woodruff, associate professor of Comparative Politics at the London School of Economics and Political Science, was interviewed at the Volkswagen Summer School “Governance, Markets, and Institutions: Russia and Germany Compared,” which took place at the Free University Berlin, September 26–October 10, 2015. As a guest lecturer, Woodruff gave a presentation, “Eurozone Governance and Global Financial Stability.” The interview was prepared by Elena Gudova, a PhD student and teacher at the Higher School of Economics. David Woodruff explains the origins of his interest in Karl Polanyi’s famous work The Great Transformation and how he applies Polanyi’s ideas to the 1990s economic reforms in Russia and the current crisis in the Eurozone. According to Prof. Woodruff, Polanyi’s work is becoming increasingly important today because it analyzes the foundations of the neoliberal market approach and government attempts to shield markets from political processes. In his book Money Unmade: Barter and the Fate of Russian Capitalism [Woodruff 2000a], Woodruff discusses barter and debt offsets in Russia before the devaluation of 1998 as a defensive reaction of society to attempts to introduce market liberalism of the sort Polanyi analyzed, employing analogous means of mitigating the price mechanism.